Why We Need Specialised Centres for Women’s Hearts: Changing the Face of Cardiovascular Care for Women - Martha Gulati; Cara Hendry; Biljana Parapid; Sharon L Mulvagh (European Cardiology Review)
Although cardiovascular disease (CVD) is the leading cause of mortality in women globally, cardiovascular care for women remains suboptimal, with poorer outcomes than for men. During the past two decades, there has been an incremental increase in research and publications on CVD in women, addressing sex-specific risk factors, symptoms, pathophysiology, treatment, prevention and identification of inequities in care. Nonetheless, once women have manifested CVD, they continue to have increasingly worse outcomes than men. An approach to addressing these global disparities has been the worldwide establishment of specialised centres providing cardiovascular care for women. These women’s heart centres (WHCs) allow a comprehensive approach to the cardiovascular care of women across the lifespan. The purpose of this article is to define the need for and role of these specialised centres by outlining sex-specific gaps in CVD care, and to provide guidance on components within WHCs that may be considered when establishing such programmes.